New data on Late Jurassic sauropods of central and northern sectors of the Bombarral Sub-basin (Lusitanian Basin, Portugal). (17th February 2017) - Mocho, P.; Royo-Torres, R.; Malafaia, E.; Escaso, F.; Narváez, I.; Ortega, F.
Abstract: The Upper Jurassic's central and northern sectors of the Bombarral Sub-basin are relatively poor in sauropod material, highlighting the specimens (mainly teeth) found in the Guimarota mine (Leiria) and the Andrés (Pombal) fossil site. The study of published and the unpublished sauropod material allows for a revision of the present state of sauropod diversity of the Bombarral Sub-basin. These new specimens come from Pombal, Leiria, Batalha, Porto de Mós, Alcobaça and Caldas da Rainha, and include an almost complete posterior or middle dorsal neural spine and a partial caudal series. The systematic re-evaluation of the sauropod record of this sector indicates the presence of turiasaurs, diplodocines, titanosauriforms and an indeterminate eusauropod form. During the last part of the twentieth century, the discovery of fossil vertebrates has increased significantly in the sediments cropping out in the central and northern sectors of the Bombarral Sub-basin (Alcobaça and Bombarral Formations), improving our understanding of the Late Jurassic faunas of the Lusitanian Basin.